The Analysis of Relational Process Realized on Descriptive Texts Taken From Senior High School Textbook - Asiyah Mumtahanah Khoiruzzahra; Andi Rustandi; Ratnawati Ratnawati (Jurnal Siliwangi: Seri Pendidikan, 2018)
This study aimed at investigating the relational process which was realized in the descriptive text used in senior high school textbooks. Relational process systems which relate to the ideational meaning could reveal the role and involve state of being (including having) between the clauses (Gerrot and Wignell, 1994, p. 67). This study employed qualitative discourse analysis to analyze descriptive texts which were taken from senior high school textbook by the writer into relational process types. In analyzing the data, the writer analyzed it into relational process as suggested by Halliday and Mathiessen (2004; 2014); and Butt et al (2000). The results of this study showed that all types of relational process which covered identifying and attributive process were used in the first, second and third text. Furthermore the attributive process was produced mostly at which it indicated that the these texts contained only one participant  which is called a carrier so it can not be in passive (reversible).